Early healing after elevation of the maxillary sinus floor applying a lateral access: a histological study in monkeys - Scala, Alessandro [UNESP]; Botticelli, Daniele [UNESP]; Rangel, Idelmo Garcia [UNESP]; Oliveira, José Américo de [UNESP]; Okamoto, Roberta [UNESP]; Lang, Niklaus Peter (Wiley-Blackwell Publishing, Inc, 2010)
AimTo describe the early healing within the void obtained after the elevation of the sinus mucosa and simultaneous implant installation without the use of any grafting material in monkeys.Material and methodsImplants were installed simultaneously with the elevation of the maxillary sinus using the lateral approach in eight monkeys without the use of grafting material. The healing after 4, 10, 20 and 30 days was evaluated in the area distal to the implants. Paraffin sections were prepared and analyzed using qualitative histological methods.ResultsThe healing process was initiated by the formation of a coagulum and followed by a provisional matrix and woven bone. Subsequently, a parallel-fiber bone replaced woven bone. The dimension of the elevated area shrank during the healing process. Sprouts of woven bone, present to a moderate extent after 4 days, were more numerous after 10 and 20 days. Newly formed bone originated from the sinus walls and septa, while there was no evidence of participation of the Schneiderian membrane in this process. After 30 days, the window access appeared to be closed by a layer of newly formed trabecular bone.ConclusionsThe coagulum that filled the void distal to the implant after simultaneous elevation of the sinus floor gave rise to newly formed bone. However, the void occupied by the coagulum shrank substantially. The Schneiderian membrane did not provide a basis for new bone formation in the early phase of healing.To cite this article:Scala A, Botticelli D, Rangel IG Jr, de Oliveira JA, Okamoto R, Lang NP. Early healing after elevation of the maxillary sinus floor applying a lateral access: a histological study in monkeys.Clin. Oral Impl. Res. 21, 2010; 1320-1326.doi: 10.1111/j.1600-0501.2009.01964.x.
Keywords: animal study; bone healing; clot; coagulum; early healing; implant dentistry; sinus elevation; sinus grafting; sinus lifting